Prescription of guideline‐directed medical therapy in heart failure: impact on mortality and readmission - Martin Möckel; Samipa Pudasaini; Kristina Feldmann; Henning Thomas Baberg; Benny Levenson; Jürgen Malzahn; Thomas Mansky; Guido Michels; Christian Günster; Elke Jeschke (ESC Heart Failure, 2025)
Abstract Aims The 2021 European heart failure (HF) guidelines recommend the combination of four drugs as a standard therapy (angiotensin‐converting enzyme inhibitor [ACEI]/angiotensin receptor blocker [ARB]/angiotensin receptor‐neprilysin inhibitor [ARNI]; beta‐blocker (BB); mineralocorticoid receptor antagonist [MRA]; sodium‐glucose co‐transporter 2 inhibitor [SGLT2i]) in patients with heart failure and reduced ejection fraction (HFrEF). We investigated if the use of this combined treatment (as opposed to the outdated two‐drug ACEI/ARB and BB therapy) yields a favourable outcome regarding mortality and readmission and evaluated whether an increase in adoption of the newly endorsed therapy can already be observed in clinical routine. Methods and results We included anonymous data from all patients who were insured at Germany’s largest health insurer (Allgemeine Ortskrankenkasse [AOK]) and had a claims record for hospitalization (2019–2021) with the main diagnosis of HF. Mortality and readmission within 91–365 days following the index stay were analysed, and the impact of medication on outcome was compared. 315 342 cases of hospitalization due to HF were included (median 80 years [IQR 72–86], 53.7% female). HF drug prescription rates were as follows: ACEI 46.3%, ARB 31.8%, ARNI 12.1%, BB 80.9%, MRA 35.6%, SGLT2i 7.3%. Treatment combinations were prescribed in 35.9% (two‐drug) and 3.7% (four‐drug). Total mortality was 18.0%, all‐cause readmission 32.0%, and HF readmission 16.0%. Mortality risk was significantly lower (adjusted HR = 0.92 [95% CI 0.86–0.97]) with the four‐ versus two‐drug treatment. Kaplan–Meier survival was 88.2% for the four‐drug therapy [95% CI: 87.6%–88.8%] and 83.1% for the two‐drug therapy [95% CI: 82.9%–83.3%]). Similar benefits were visible for the readmission rates due to all causes (HR = 0.76 [0.73–0.80]) and readmission due to HF (HR = 0.90 [0.85–0.95]). Conclusions Our study suggests that the newly recommended four‐drug therapy may lead to lower mortality and readmission rates compared to the outdated two‐drug therapy. However, the overall adoption of the four‐drug therapy remains limited.